2017
DOI: 10.1016/j.vaccine.2017.07.061
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of the doubt or doubts over benefits? A systematic literature review of perceived risks of vaccines in European populations

Abstract: Findings: A total of 145 articles were selected, most of which were conducted in the UK, the Netherlands and France and studied seasonal influenza, HPV and pandemic influenza vaccination. Across all countries and vaccines, the primary area of concern was vaccine safety, followed by perceptions of low likelihood of contracting vaccine-preventable diseases (VPDs), perceived low severity of VPDs, beliefs that vaccines do not work, and overall lack of information. Concerns were found to be vaccine-, country-and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
206
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(247 citation statements)
references
References 155 publications
(276 reference statements)
12
206
0
16
Order By: Relevance
“…This can be related to the perceived scarcity of e cacy studies or a lack of clear information about the infection and the vaccine. (27) The low perception of the safety of HPV vaccine, among vaccine hesitant nurses is consistent with a study that found that primary healthcare professionals had been receiving contradictory information about the effectiveness and e cacy of this vaccine. (28) Another differential factor between hesitant and non-hesitant was the low perception of the severity of immuno-preventable diseases.…”
Section: Discussionsupporting
confidence: 68%
“…This can be related to the perceived scarcity of e cacy studies or a lack of clear information about the infection and the vaccine. (27) The low perception of the safety of HPV vaccine, among vaccine hesitant nurses is consistent with a study that found that primary healthcare professionals had been receiving contradictory information about the effectiveness and e cacy of this vaccine. (28) Another differential factor between hesitant and non-hesitant was the low perception of the severity of immuno-preventable diseases.…”
Section: Discussionsupporting
confidence: 68%
“…This was possible due to the combined action of the early screening through the Papanicolaou test and prophylactic vaccination with HPV vaccines. Three HPV vaccines are now available: Cervarix (HPV 16 and 18), Gardasil (HPV 6,11,16,18) and Gardasil 9 (HPV 6,11,16,18,31,33,45,52,58). Several studies have emphasized the efficacy and safety of these vaccines [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, their safety profiles have been debated due to the growth of antivaccine movements, and there have been numerous controversies regarding their adverse events following immunization (AEFI). A systematic review investigating the perceived risk of vaccines in Europe [16] underlined the high number of safety concerns about HPV vaccination: in 29 articles analysed, the most common concerns were about the safety. On 26 May 2016, C. Gøtzsche and others of the Nordic Cochrane Centre, made a complaint over how the European Medicines Agency handled the safety assessment of HPV vaccines [17].…”
Section: Introductionmentioning
confidence: 99%
“…Se le estima como una de las herramientas más costo-efectiva para disminuir la tasa de las enfermedades inmunoprevenibles, lo que ha sido demostrado tras la implementación de campañas y programas de inmunización que han permitido reducir de manera significativa la morbilidad, discapacidad y mortalidad de la población a causa de la enfermedades prevenibles a través de la vacunación [1][2][3][4][5][6] . Sin embargo, en los últimos años han aumentado los cuestionamientos, la información falsa, el escepticismo, y la desconfianza en cuanto a la utilidad, seguridad y efectividad de las vacunas, convirtiéndose en un desafío global para todos los programas de inmunización, con una posible repercusión nacional [7][8][9][10] .…”
Section: Cavei Considerations For the Promotion Of Vaccination Adherenceunclassified